Verificação da eficiência de armaduras de cantos - Domingues, Lídia da Conceição (1974)
Verify the behaviour of rightangle corners formed by reinforced concrete plates when subjected to tensile stresses on the inside faces. Sixteen test specimens presenting two types of details largely used in Brazil were tested. The influence of different percentages of inclined reinforcement placed or not in haunch was investigated for one of these details. Comparisons were made among the tested specimens focusing the efficiency, cracking under working loads and stiffness in order to determine which one of the tested details would yield the best performance.